Motivación al logro y motivación al poder en el contenido de historietas populares - Escovar, Luis A.; de Escovar, Peggy L. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
An analysis of the contents of comic books was made, using a sample of 24 comic magazines which are representative of those magazines with the largest circulation in Panama. The findings indicate that the level of power motivation is significantly higher than the level of achievement motivation. Furthermore, the findings indicate that the achievement motive is essentially nonexistent in the content of the comic books. These findings are interpreted in the context of McClelland’s theory of economic development (1961). It is conjectured that the presentation of a structure of motivation geared toward power and in which there does not exist achievement motivation is potentially detrimental to the economic development of a country.